EMAS and ISO 14001 : implementation case studies - Victory, Kathleen M. (Arlington, 1999)
"The report is a fast, cost-effective way to examine the experiences of companies and municipalities that have put environmental management systems into practice. The report features the experiences of over 30 companies from North America, Europe and Asia. It describes the pilot experiences that municipalities and local authorities have had so far with EMAS and ISO 14001 and compares the implementation experiences of large and small firms. The report details implementation costs and presents results from a number of international surveys on the motivations for certification to EMAS and ISO 14001."